(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The article presents the outcome of a study on the role a victim plays in originating the crime of rape. The aim of the study was to determine if and in what manner the victim contributes to conceiving and accomplishment of criminal intent. Accordingly, the scholars attempt at selection and specification of factors behind the predisposition of a person to become a victim of a rape, since this can be conducive to the committal of the crime. The article covers all that has been determined with regard to the behaviour of victims before the crime was committed, particularly that which directly bore on them being chosen an object of perpetrator’s attack. Further, it has been shown how the victim’s contribution to the committal of the rape is due to the victim’s certain socio-psychic features, and an earlier relationship, particularly of personal nature, with the perpetrator. Next, the problem of resistance or nonresistance on the part of the victim during the attack has been discussed in relation to the interpretation of this resistance by the perpetrator (the problem of actual or simulated resistance). A survey has also been made of recent trends to change the methodology and assessment of research on rape victims, arising due to the discussion on psychological and social effects of rapes on their victims. Hence ensuing conclusions are applicable in practice, particularly with regard to: 1) the improvement of the operation of the prosecuting organs and the administration of justice, 2) increased knowledge on the causes of rapes, and 3) possibilities of further development of methods towards efficient preventiveness and fight against these crimes.